Lanthanide-sensitized lanthanide luminescence: terbium-sensitized ytterbium luminescence in a trinuclear complex. - Faulkner, S; Pope, S (2003)
A heterotrinuclear lanthanide complex has been prepared which contains two terbium ions in DO3A-derived binding sites and a single ytterbium ion in a DTPA-like site. The luminescence properties of the system have been investigated, showing that the terbium remains in a seven-coordinate binding site throughout the synthesis, while the ytterbium occupies the eight-coordinate site. Pumping the 488 nm absorption band of the terbium ion results in energy transfer to ytterbium with emission at 980 nm.